2022
DOI: 10.3389/fonc.2022.893282
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Chemoresistant Risk Scoring Model for Prechemotherapy Osteosarcoma Using Single-Cell Sequencing

Abstract: BackgroundChemoresistance is one of the leading causes that severely limits the success of osteosarcoma treatment. Evaluating chemoresistance before chemotherapy poses a new challenge for researchers. We established an effective chemoresistance risk scoring model for prechemotherapy osteosarcoma using single-cell sequencing.MethodsWe comprehensively analyzed osteosarcoma data from the bulk mRNA sequencing dataset TARGET-OS and the single-cell RNA sequencing (scRNA-seq) dataset GSE162454. Chemoresistant tumor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…Zhou et al examined the scRNA-seq landscape of intratumoral heterogeneity and revealed an immunosuppressive microenvironment in advanced OS ( 17 ). Recently, Zeng et al developed a chemo-resistant risk-scoring model for pre-chemotherapy OS by analyzing a scRNA-seq database ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al examined the scRNA-seq landscape of intratumoral heterogeneity and revealed an immunosuppressive microenvironment in advanced OS ( 17 ). Recently, Zeng et al developed a chemo-resistant risk-scoring model for pre-chemotherapy OS by analyzing a scRNA-seq database ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting clinical and experimental data suggests that osteosarcoma stem cells, which originate from mesenchymal stem cells, may be the biological genesis of osteosarcomas and demonstrate osteoblastic differentiation, producing malignant osteoid ( Brown et al, 2017 ; Xi et al, 2000 ). In addition, osteosarcoma is strongly connected with the osteoblastic lineage and displays osteogenic differentiation-related activities in proliferation, extracellular matrix secretion, and induction of ossification ( Zeng et al, 2022 ). So, in this study, potential cellular communication networks among mesenchymal stem cells, proliferating osteoblastic cells, and osteoblastic cells were identified through comprehensive analysis of osteosarcoma single-cell RNA sequencing (scRNA-seq), illustrating the complex regulatory network in the advanced osteosarcoma microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The CellphoneDB ( 46 ) algorithm and R ‘iTALK’ (version 0.1.0) ( 47 ) package were used to evaluate the crosstalk across the immunological and non-immunological cellular components in normal mucosa, tumor adjacent and tumor tissue. The quantification of cell-cell communications by calculating the expression of immune checkpoint genes using ‘iTALK’ has been reported in previous studies ( 48 , 49 ). The expression level of immune checkpoints is a key factor in the remodeling of tumor immune microenvironment and immunotherapy response, and the quantile or custom-defined values of PD-L1 expression were associated with patient outcomes after immunotherapy in lung cancers and colorectal cancers ( 50 , 51 ).…”
Section: Methodsmentioning
confidence: 99%